A Study on Service Quality and Passenger Satisfaction on Indian Airlines - Singaravelu, K; Amuthanayaki, V. P (Journal of Commerce and Trade, 2017)
This study examines the underlying forces of service quality influences on passengers’ satisfaction in aircraft transport. The study examines which dimensions have a positive influence on service quality and which dimensions have the most and least important impact on service quality in international air travel, as perceived by airline passengers. The findings of this study are based on the analysis of sample respondents. This study analyzed the data from passengers of three classes, economy, business and premium. The results suggest that there are different factors of in-flight service quality that are important according to the customer seat class. The dimensionality of perceived service quality in international air travel was explored and three dimensions were identified. These dimensions include in-flight service, in-flight digital service and back-office operations. The findings reveal that these three dimensions are positively related to perceive service quality in international air travel and of these dimensions, Cuisines provided, seat comfort safety are the most important dimension in in-flight service quality. Personal entertainment is the most important dimension as perceived by airline passengers in In-flight digital service quality. Online ticket booking is another dimension in back-office operations. In addition, the findings indicate that passengers’ satisfaction on different airline companies on basis of the services delivered. JEL Classification : D 18, L 83, L 93.